ANALISIS PENGUJIAN KEWAJARAN DAN KELAZIMAN USAHA ATAS TRANSAKSI ROYALTI LISENSI PADA PT ABC - Fazhilla Roza Sabrina (Universitas 45 Surabaya, 2023)
This study aims to find out how to determine the method used in determining the fairness and customary business of PT ABC's royalty payment transactions to the parent company, namely XYZ and the suitability of transfer pricing with tax provisions on transactions for royalty payments. The method in this study is to use a qualitative approach by looking at various sources, including books, documents, national and international journals and laws related to the topic of transfer pricing. The results of this study conclude that the determination of fair prices by PT ABC is to carry out a comparability analysis by taking external data as a comparison, choosing the Comparable Uncontrolled Price (CUP) method as a method of determining transfer prices and applying the principles of fairness and business practice by using a royalty range.